Impact street earnings on tax avoidance - Yohana; Zulfikar Ikhsan Pane (Directorate General of Taxes, 2024)
This study discusses the effect of street earnings on tax avoidance for two reasons. First, there is the potential for companies that always minimize tax avoidance, especially after the COVID-19 pandemic. Second, preventive actions from various parties, including independent commissioners, public accounting firms, and securities analysts who carry out street earnings-related tax avoidance activity. This study was conducted on manufacturing companies for the 2015–2020 period. This study also added an expansive test without taking two controlling variables. As a result, street earnings have a significant negative effect on tax avoidance in expansive testing, meaning recommended companies by analysts could potentially do tax avoidance. The practical implication is the role of securities analysts as recommended parties for company monitoring. The theoretical implication is that transitory items excluded increase earnings relevant in various tests, thus further studies are needed, such as the effect of street earnings on corporate governance.